2017
DOI: 10.1016/j.metabol.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors: Shaping the future after the further cardiovascular outcomes research with PCSK9 inhibition in subjects with elevated risk (FOURIER) trial

Abstract: Proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors have been shown to decrease low-density lipoprotein cholesterol (LDL-C) levels by about 60% on top of statin therapy [1]. Apart from LDL-C, PCSK9 inhibitors also increase high-density lipoprotein cholesterol (HDL-C) and reduce triglycerides (TGs), non-HDL-C and lipoprotein (a) [Lp(a)] levels, potentially lowering residual cardiovascular (CV) risk [2,3]. In terms of safety, PCSK9 inhibitors did not increase the risk for severe adverse events, stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…In COVID-19-positive patients, the majority of baseline CVD is of atherosclerosis origin, with the worst prognosis for patients being at the high, and especially very high and extremely high, risk of CVD [16]; thus, intensive LLT with statins and/or fixed combination with ezetimibe and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors seems to be critical. Indeed, we should do our best to maximally improve therapy adherence and thus have a better prognosis for the infected CVD patients [44,45]. In this context, there are no premises that PCSK9 inhibitors, because they are monoclonal antibodies (in relation to the above-mentioned high cytokine storm during infection), should be discontinued.…”
mentioning
confidence: 99%
“…In COVID-19-positive patients, the majority of baseline CVD is of atherosclerosis origin, with the worst prognosis for patients being at the high, and especially very high and extremely high, risk of CVD [16]; thus, intensive LLT with statins and/or fixed combination with ezetimibe and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors seems to be critical. Indeed, we should do our best to maximally improve therapy adherence and thus have a better prognosis for the infected CVD patients [44,45]. In this context, there are no premises that PCSK9 inhibitors, because they are monoclonal antibodies (in relation to the above-mentioned high cytokine storm during infection), should be discontinued.…”
mentioning
confidence: 99%
“…This study also aids with the cost-effectiveness analysis of drugs (51)(52)(53). When two PCSK9 inhibitors became commercially available in 2015, they did improve the clinical prognosis for secondary prevention, but the annual retail cost was nearly $14,000.…”
Section: Discussionmentioning
confidence: 84%
“…Two mAbs for LDL-C reduction, evolocumab and alirocumab, have been permitted by both the FDA and European Medicines Agency and both have affirmed a notable ability in reducing LDL-C along with a promising safety profile (6). Additionally, according to the Further Cardiovascular Outcomes Research that reported the PCSK9 inhibition in patients with elevated risk trial (7), patients presenting high cardiovascular risk were investigated at first. Evolocumab has been proven to decrease cardiovascular episodes.…”
Section: Resultsmentioning
confidence: 99%